The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1152/japplphysiol.01622.2011
|View full text |Cite
|
Sign up to set email alerts
|

The combination of theophylline and endothelin receptor antagonism improves exercise performance of rats under simulated high altitude

Abstract: Decreased physical performance is a well-known consequence of rapid ascent to high altitude. Hypoxic pulmonary vasoconstriction (HPV) potentially limits cardiac output and systemic blood flow, thus preventing successful adaptation to rapid ascent. We hypothesized that pharmacological enhancement of the heart rate with theophylline, combined with reversal of HPV via endothelin blockade, could increase exercise performance at high altitude. Female Sprague-Dawley rats were treated with combinations of 1) theophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…We have selected anesthetic regimen that are known, and confirmed by our data, to have a comparably small effect on the cardiovascular system, as ketamine/xylazine does not affect the heart rate and only slightly reduce mean arterial pressure at higher doses [43]–[45]. While it is clear that cardiovascular differences between anesthetized resting and awake exercising animals are drastic, effects of hypoxia on the organism, such as hypoxemia, and hypoxic pulmonary vasoconstriction, and sympathetic activation are found in both states [10], [45]. This is demonstrated e.g.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We have selected anesthetic regimen that are known, and confirmed by our data, to have a comparably small effect on the cardiovascular system, as ketamine/xylazine does not affect the heart rate and only slightly reduce mean arterial pressure at higher doses [43]–[45]. While it is clear that cardiovascular differences between anesthetized resting and awake exercising animals are drastic, effects of hypoxia on the organism, such as hypoxemia, and hypoxic pulmonary vasoconstriction, and sympathetic activation are found in both states [10], [45]. This is demonstrated e.g.…”
Section: Discussionsupporting
confidence: 79%
“…Briefly, rats were habituated to running in a motorized wheel system (Lafayette Instruments, Lafayette, IN) at 10 min/day for approximately 10 days, and then subjected to exercise testing in the same wheels in a hypobaric chamber at the Duke University Center for Hyperbaric Medicine and Environmental Physiology. The chosen level of simulated high altitude of 4267 m has been shown to strongly decrease voluntary performance in the rat [10]. Treatment agents were injected at near sea level altitude (119 m) 30 minutes before starting the exercise protocol, and the rats were taken to altitude 15 minutes before starting the run to allow for 5–10 minutes of equilibration time at altitude before exercise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary window method has also been tested for its ability to report changes in blood flow velocity in the metastatic lesion, by measuring the effect of a pharmacological treatment that has recently been found to increase blood flow velocity in the pulmonary circulation: the hypertensive drug ephedrine increases cardiac output, whereas the endothelin receptor blocker ambrisentan reduces the pre-capillary arteriolar tone, which results, when the drugs are given in combination, in increased blood flow velocity in pulmonary capillaries. While these data are currently under review elsewhere, the ability of the combination of a hypertensive drug and an endothelin receptor antagonist to increase peripheral muscular perfusion has been published independently 18 . While under normal conditions, a dose-dependent increase of blood flow velocity can be observed after both injections, the fact that the second injection does not lead to a further increase of flow velocity in sarcoma metastases might result from the fact that maximal tumor vessels vasodilation has already been reached after the first combined injection of ephedrine and ambrisentan.…”
Section: Discussionmentioning
confidence: 99%
“…recently demonstrated that the combination of the xanthine drug theophylline and an endothelinblocking vasodilator improves exercise performance capacity of hypoxemic rats (Radiloff et al 2012).…”
Section: R a F Tmentioning
confidence: 99%